Európa az öregedés útján vagy talán a „fiatalodás" lépcsőjén? - Suti, Zoltán (Közép-Európai Közlemények, 2009)
The ageing wave of Europe is going to have its effects also on other parts of the world as soon as within a few decades. The question is whether the inhabitants of the European states and those of the other continents are able to follow this dynamic change, react on it considering individual and collective responsibility without a hotspot, and adjust the reforms to the demographic forecast. Is there a solution for these problems? The latest surveys are widening the gaps on social network and services and the researchers have put the changes in society forward in the process of searching. The progress of cultural evolution often comes face to face with the labour market’s reforms and pension schemes – eager to be changed– blocks the possibility of growing GDP for decades.